Pengaruh Rekrutmen Dan Penempatan Kerja Terhadap Kinerja Karyawan Pada PT Sinergi Aitikom Jakarta Selatan - Sifa Fauziah; Sri Mulyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the effect of recruitment and job placement on employee performance at PT Sinergi Aitikom, South Jakarta. The background of this research lies in the importance of human resource management in achieving organizational goals. Effective recruitment and proper job placement are believed to improve employee performance, yet in practice, companies often face challenges in selecting qualified candidates and assigning employees to positions that match their competencies. This research employed a quantitative method with a questionnaire as the main instrument. The population consisted of all employees at PT Sinergi Aitikom, with 81 respondents selected using a saturated sampling technique. The data were analyzed using validity and reliability tests, multiple linear regression analysis, t-test, F-test, and the coefficient of determination (R²). The results show that: (1) recruitment has a positive and significant effect on employee performance, with a t-value of 9.626 > t-table 1.990, a significance level of 0.000, and a regression coefficient of 0.757; (2) job placement has a positive and significant effect on employee performance, with a t-value of 10.645 > t-table 1.990, a significance level of 0.000, and a regression coefficient of 0.701; (3) recruitment and job placement simultaneously have a significant effect on employee performance, as indicated by an F-value of 77.268 > F-table 2.720, a significance level of 0.000, and a coefficient of determination (R²) of 0.656 or 65.6%. Thus, it can be concluded that recruitment and job placement play an important role in improving employee performance. The company is advised to strengthen its recruitment system, ensure job placement aligns with employee competencies.